(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
In the article the modern challenges faced by the higher education system in Ukraine due to the pandemic and Russian military aggression are analyzed. The advantages and disadvantages of implementing distance education in the conditions of modern emergency and crisis situations in the country are presented. Particular attention is devoted to the description of the advantages and disadvantages of the professional training of higher education students of the specialties 014 Secondary Education (Physical Culture) and 017 Physical Culture and Sports in the conditions of distance learning. Attention is focused on the fact that despite all the benefits of the distance learning system, future physical culture teachers and trainers do not have the opportunity to qualitatively master the rational technique of movements from various sports. Despite access to video materials with a demonstration of the reference technique for performing the exercise as a whole and its individual elements, students have limited opportunities for its high-quality consolidation and practice. When students independently study the technique of movements, the teacher does not always can correct technical errors and provide meaningful methodical recommendations, which as a result can lead to the formation of stereotypically incorrect movements of the students of the specified specialties when performing certain exercises. In this context teachers of practice-oriented disciplines are recommended to actively use modern digital technologies and other forms of digital technologies in their work, which allow correcting errors in the execution of exercise techniques and monitoring the physical activity of each student in real time. Despite a few shortcomings of the distance learning system, it remains the only alternative and safe form of obtaining higher education in Ukraine and an effective tool for realizing the constitutional right of the citizens to obtain education and professional qualifications.